2002
DOI: 10.1093/brain/awf254
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL induces death of human oligodendrocytes isolated from adult brain

Abstract: Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) has been reported to induce apoptosis in various tumour cell lines and, recently, also in normal cells. TRAIL interacts with four receptors: two signalling receptors (TRAIL-R1 and TRAIL-R2) and two decoy receptors (TRAIL-R3 and TRAIL-R4). We have shown that both signalling receptors are present on the surface of oligodendrocytes isolated from adult human brain (ahOL), whereas the decoy receptors are expressed at a low level on ahOL. TRAIL induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 39 publications
3
42
0
2
Order By: Relevance
“…In line with previous data, 28 Reverse transcriptase-PCR (RT-PCR) analysis for mRNAs and Western blot analysis for proteins showed that MO3.13 cells express both DR4 and DR5 receptors (Figure 1a and b). In the experiments, HeLa cell samples were used as internal positive controls.…”
Section: Trail Receptors Are Expressed By Human Oligodendrocytic Cellsupporting
confidence: 91%
See 3 more Smart Citations
“…In line with previous data, 28 Reverse transcriptase-PCR (RT-PCR) analysis for mRNAs and Western blot analysis for proteins showed that MO3.13 cells express both DR4 and DR5 receptors (Figure 1a and b). In the experiments, HeLa cell samples were used as internal positive controls.…”
Section: Trail Receptors Are Expressed By Human Oligodendrocytic Cellsupporting
confidence: 91%
“…As TRAIL represents a substantial cause of oligodendrocyte death, 28 in order to confirm specificity of such effect, we first studied whether the MO3.13 cell line expressed the two TRAIL receptors DR4 and DR5. In line with previous data, 28 Reverse transcriptase-PCR (RT-PCR) analysis for mRNAs and Western blot analysis for proteins showed that MO3.13 cells express both DR4 and DR5 receptors (Figure 1a and b).…”
Section: Trail Receptors Are Expressed By Human Oligodendrocytic Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…55 Thus, by combining the two, one has a single agent that could in principle impact both priming and later phases of the disease. 4) One group has reported that TRAIL may contribute to death of neurons after the priming phase, 70,73 in keeping with previous studies showing that both primary human neurons 74 and oligodendrocytes 75 are susceptible to TRAIL-induced cell death. By coupling Fn14 to TRAIL, one is providing an agent that sustains the integrity of the BBB (via TWEAK blockade) and thereby mitigates TRAIL's access to the CNS.…”
Section: Discussionsupporting
confidence: 68%